Cum causa matrimonialis sit de maximis causis... Per uno studio degli acta giudiziari nel Patriarcato d’Aquileia: le cause matrimoniali dalla metà del XIII agli inizi del XIV secolo - Blancato, Sebastiano (Scrineum, 2017)
This  paper is intended as a first study of judicial acts of  matrimonial cause proceedings in the Patriarchate of  Aquileia. It  consists of an introductory note and an Appendix. The former   firstly deals with the heuristic peculiarities of this branch of documentary sources and with  the wedding institution in the  late Middle Ages and its impediments according to canon laws; secondly,  it gives an account of the Friulian documents of wedding  contracts from the second half of the 13th century to the first decades of the 14th century and of the procedural acts, with specific attention to the places of law courts, the people involved, the procedural iter and the documentary praxis inferred from the documents. In the Appendix 10 procedural dossiers and 12 individual documents, mostly yet unknown, are published.